HUBUNGAN KECEPATAN LARI DAN DAYA LEDAK OTOT TUNGKAI TERHADAP KEMAMPUAN LOMPAT JAUH PADA SISWA KELAS VIII SMPN 1 PRAYA BARAT DAYA KABUPATEN LOMBOK TENGAH TAHUN PELAJARAN 2019/2020 - Zakir Burhan (LPPM Institut Pendidikan Nusantara Global, 2020)
The Long jump is a jump event contested in athletic. To be a long jumper a few factors that must be met such as physical, technical and mental. Every sports activites both race, game, and definitly requires competition physical condition named speed. An effort to achieve the maximum distance of jumps, a jumpers is required to have the speed and power required at the time took in approach and a foothold in the started. The productof speed and strenght is explosive power. The aim of this research is to know correlation between speed running andexplosive power Of Limbs onLong Jump abilitytoward VIII Grade students SMPN 1 Southwestern Praya Central Lombok in 2019/2020. This study use a double design, the population of this study was proportional random sampling with population number is 79, and the sample is 28 chosing and proportional random sampling. The data analysis technique used was SPSS 17.0. Based on the results of data analysis, it can be concludes that there is a significant Correlation between Running Speed and Explosive power of Limbs to long jump ability, provenR count (R˳) = 1,000 after significant test using the F test,the obtained Sig.Is smaller than a = 0.00 <∝ 0.05).